2020
DOI: 10.3390/su12229738
|View full text |Cite
|
Sign up to set email alerts
|

Combining Eco-Design and LCA as Decision-Making Process to Prevent Plastics in Packaging Application

Abstract: The diffusion of the culture of sustainability and circular economy increasingly pushes companies to adopt green strategies and integrate circular business models in the corporate agenda. It assumes higher relevance in the packaging industry because of the growing plastics demand, the increasing awareness of consumers on single-use-products, the low recyclability performance and last but not least, the challenge of urban littering and microplastics dispersion in marine ecosystem. This paper presents the case o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Despite the large efforts dedicated to making the transition towards a more circular economy, an important challenge remains in assessing the recyclability of plastics (e.g., [22]). A reduced level of recyclability of plastics can result (i) from the difficulty to separate different plastic types [23], (ii) from the heterogeneity and mixing of collected plastic fractions, (iii) from degradation processes during the recycling process that impact crucial mechanical properties of recycled plastics [24,25], (iv) from the efforts related to the recycling processes (e.g., [26])) and (v) from the presence of adverse effects; e.g., contaminations and the accumulation of substances in the recyclate that may pose a health risk [27]. This shows that assessing plastic recyclability is a complex task that requires further research.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the large efforts dedicated to making the transition towards a more circular economy, an important challenge remains in assessing the recyclability of plastics (e.g., [22]). A reduced level of recyclability of plastics can result (i) from the difficulty to separate different plastic types [23], (ii) from the heterogeneity and mixing of collected plastic fractions, (iii) from degradation processes during the recycling process that impact crucial mechanical properties of recycled plastics [24,25], (iv) from the efforts related to the recycling processes (e.g., [26])) and (v) from the presence of adverse effects; e.g., contaminations and the accumulation of substances in the recyclate that may pose a health risk [27]. This shows that assessing plastic recyclability is a complex task that requires further research.…”
Section: Introductionmentioning
confidence: 99%
“…Life cycle assessment (LCA) can be a helpful tool in Ecodesign if integrated into the company structure [2] and can be used to improve the environmental performance and determine the sustainability baseline of products [3,4]. LCA and Ecodesign can be combined simultaneously to examine and validate product redesign and decision making [5,6]. However, the study of Lindahl [7] showed that only 18% of engineering designer respondents applied LCA as a method or tool in their design for the environment in companies.…”
Section: Introductionmentioning
confidence: 99%
“…The issue of sustainability is getting more attention from the world authorities related to the issue of ensuring responsible consumption and production patterns, including food production. The mixture of sustainability and business practice significantly drives industries to take up nature strategies in their business model (Foschi, Zanni and Bonoli, 2020). Nowadays, food production deals with immense hindrance from sustaining food qualities to protecting weather conditions and environment (Neethirajan et al 2018).…”
Section: Introductionmentioning
confidence: 99%